Major Dietary Patterns in Relation to Stunting among Children in Tehran, Iran - Esfarjani, Fatemeh; Roustaee, Roshanak; Roustaee, Roshanak; Mohammadi-Nasrabadi, Fatemah; Mohammadi-Nasrabadi, Fatemah; Esmaillzadeh, Ahmad; Esmaillzadeh, Ahmad (Journal of Health, Population and Nutrition, 2013)
To the best of our knowledge, no information is available to link major dietary patterns to stunting during childhood, although dietary patterns are associated with chronic diseases. This study was conducted to determine the relationship between major dietary patterns and stunting in the first grade pupils of Tehran in 2009. In this case-control study, 86 stunted children (defined as height-for-age of less than the 5th percentile of CDC2000 cutoff points) were enrolled from among 3,147 first grade pupils of Tehran, selected using a multistage cluster random-sampling method. Participants for the control group (n=308) were selected randomly from non-stunted children (height-for-age more than the 5th percentile of CDC2000 cutoff points), after matching for age, sex, and area of residence. Dietary data were collected using two 24- hour dietary recalls through face-to-face interview with mothers. Factor analysis was used for identifying major dietary patterns. Mean consumption of dairy products (308}167 vs 382}232 g/day, p<0.05), dried fruits and nuts (2.58}9 vs 7.15}26 g/day, p<0.05) were significantly lower among stunted children than those in the control group. Three major dietary patterns were identified: traditional dietary pattern that was dominated by bread, potato, fats, eggs, flavours, vegetables other than leafy ones, sugar, drinks, and fast food; mixed dietary pattern that was dominated by leafy vegetables, fast foods, nuts, fats, cereals other than bread, fruits, legumes, visceral meats, sugars, eggs, and vegetables other than leafy vegetables; and carbohydrate-protein pattern that was dominated by sweets and desserts, poultry, dairy, fruits, legumes, and visceral meats. No significant relationships were found between traditional and mixed dietary patterns and stunting. Individuals in the third quartile of carbohydrate-protein dietary pattern were less likely to be stunted compared to those in the bottom quartile (OR: 0.31, 95% CI 0.13-0.78, p<0.05). Adherence to dietary patterns high in protein (e.g. dairy, legumes, and meat products) and carbohydrates (e.g. fruits, sweets, and desserts) might be associated with reduced odds of being stunted among children. J HEALTH POPUL NUTR 2013 Jun; 31(2): 202-210 DOI: http://dx.doi.org/10.3329/jhpn.v31i2.16384